PENERAPAN APLIKASI INLISLITE BERBASIS SISTEM INFORMASI MANAJEMEN DI SMKN 1 PRAYA TENGAH - M Sya’bani Purnama; Joni Rakhmad; Dadi Setiadi (Jurnal Ilmiah Global Education, 2022)
This study aims to describe what impacts occur when implementing the Inlislite application system based on a management information system in the library of SMKN 1 Praya Tengah. This study uses a qualitative research design and is analyzed by making rich and thick descriptions. Research at the data collection stage uses a grounded theory approach. Based on the results of the research, it can be concluded that Inlislite has a positive impact, because it can improve library services at SMKN 1 Praya Tengah because librarians process data on borrowing and returning books faster. In addition, there were technical problems in implementing inlislite at SMKN 1 Praya Tengah which resulted in the existing system running slowly. The recommendations for this research are: 1) To separate schools from Inlislite, and add library facilities in the form of the latest generation of computers; 2) Provide regular Inlislite training and guidance to Librarians, so that Librarians are more adept at operating Inlislite.